Clinical relevance of deferasirox trough levels in β‐thalassemia patients. (4th December 2017) - Allegra, Sarah; Massano, Davide; De Francia, Silvia; Longo, Filomena; Piccione, Francesca; Pirro, Elisa; Cusato, Jessica; D'Avolio, Antonio; Piga, Antonio
Summary: We evaluated the role of deferasirox therapeutic drug monitoring in order to avoid toxicity or treatment failure. Plasma concentrations, measured between two consecutive liver iron determinations, were determined at the end of dosing interval. Fifty‐four β‐thalassemic adult patients were enrolled: 50% were males; median age was 32.3 years (IQR 19.1‐41.7 years) and median body mass index was 22.25 kg/m 2 (IQR 20.24‐23.75 kg/m 2 ). The mean deferasirox dose was 28.6 ± 6.3 mg/kg/d and mean plasma concentration was 17.3 ± 16.8 μg/mL. Drug levels showed lower results in males. Deferasirox concentration was significantly correlated with serum creatinine levels ( P = .01) and serum ferritin ( P < .0001). The assessment of deferasirox therapeutic drug monitoring could help clinicians to predict patient responses and to optimize the therapy.